Model of a health program for people with disability: Flagging the need, not the disability. Issue 2 (2nd April 2020) - Puccetti, Luca; Nerattini, Marco; Quercioli, Cecilia; Sancasciani, Simonetta; Lo Presti, Eluisa; Mechi, Maria Teresa
ABSTRACT: Background: Evidence from international studies suggests that ward culture, staff attitudes, and knowledge are crucial to ensuring that hospitals adopt "reasonable adjustments" to guarantee equity of access to vulnerable patients. Among the major barriers to providing reasonable adjustments highlighted in the literature is the lack of effective systems to identify patients with disabilities and flag them in the system. Method: In November 2016, the Tuscany Regional Health System (TRHS) Government (Italy) set up a multidisciplinary working group, which used virtual collaboration methods. Results: A structured system for the early identification of patients with disabilities and their special needs, and consequent reasonable adjustments to be implemented at the hospital level, was developed. Conclusion: The project recommended two innovations: the development of a measure that grades the need of reasonable adjustments and produces a score; the possibility of entering the information for the computation of the score directly through the TRHS website.